2018
DOI: 10.1016/j.isci.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Metabolite Indole Inhibits Regeneration of the Planarian Flatworm Dugesia japonica

Abstract: SummaryPlanarian flatworms have been used for over a century as models for regeneration. Planarians live in aquatic environments with constant exposure to microbes, but the mechanisms by which bacteria may mediate planarian regeneration are largely unknown. We characterized the microbiome of laboratory populations of the planarian Dugesia japonica and determined how individual bacteria impact D. japonica regeneration. Eight to ten taxa in the phyla Bacteroidetes and Proteobacteria consistently occur across pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Trp-derived metabolites function in diverse situations. As for tissue regeneration, a recent planarian study implied the involvement of indole, a Trp catabolite via the microbiome, impaired regeneration ( Lee et al., 2018 ). Ischemia by cardiac arrest is reported to change the plasma KynA level in rats, pigs, and humans ( Ristagno et al., 2013 ), and a study reported that KynA has a protective effect against ischemic tissue damage ( Olenchock et al., 2016 ), which supports our idea that KynA regulates tissue repair non-autonomously.…”
Section: Discussionmentioning
confidence: 99%
“…Trp-derived metabolites function in diverse situations. As for tissue regeneration, a recent planarian study implied the involvement of indole, a Trp catabolite via the microbiome, impaired regeneration ( Lee et al., 2018 ). Ischemia by cardiac arrest is reported to change the plasma KynA level in rats, pigs, and humans ( Ristagno et al., 2013 ), and a study reported that KynA has a protective effect against ischemic tissue damage ( Olenchock et al., 2016 ), which supports our idea that KynA regulates tissue repair non-autonomously.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, high doses of indole in the growth medium modulate root growth by interacting with the auxinsignaling machinery (Bailly et al, 2014). Indole can also act as an intracellular signaling molecule in bacteria (Kim and Park, 2015) and suppress regeneration of the planarian worm Dugesia japonica (Lee et al, 2018), suggesting that it is a modulator of a wide variety of physiological processes in different organisms.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32] The effect of structurally different compounds was assessed on planarian growth. Some studies reported a negative effect of indole on planarian regeneration, [33] as well as an improvement in growth produced by F neuropeptide. [28] Also, melatonin was found to selectively reduce the mitotic activity of cells in the anterior portion of the planarians, without effect on posterior end's regeneration.…”
Section: Resultsmentioning
confidence: 99%